Reconstruction of Religious Awareness for Commercial Sex Workers Through a Humanistic Approach in “Lokalisasi Puger”-Jember Regency - Mohamad Hamzah; Kurniawan Ramadhani (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
Commercial sex workers (so called PSK) referred to women who have been humiliated by the public and considered social filth. Society has viewed the life of commercial sex workers (PSK) obliquely, because their lives collide with social and religious norms. The localization of Puger, Jember Regency is an isolated place which is one of the biggest prostitution places in Jember. This research used a descriptive qualitative approach with a case study design. Data collection techniques using active participatory observation, semi-structured interviews and documentation. The data analysis used was a qualitative descriptive analysis with an interactive model based on Miles, Huberman and Saldana. The validity of the data uses triangulation of sources and techniques. The research findings show that the reconstruction of akidah awareness for commercial sex workers through a humanistic approach in the localization of Puger has changed sex workers to improve and change their lives for the better, sex workers need spiritual sacredness to believe in God and leave a space where God want to be institutionalized through religious practices such as prayer, zakat, fasting and reciting the Qur’an, there are several changes in the moral aspects of sex workers, including that they do not consume drugs or alcohol, do not gamble, do not disturb neighbors with karaoke noises and their shaking, do not watch porn videos and happy to help others.